Pertimbangan Hakim Dalam Gugatan Wanprestasi Atas Uang Jaminan Deposito Ibadah Umrah - Siti Rusdiana; Erlina Bachri; Anggalana Anggalana (Peneliti.net, 2026)
This research is motivated the rise of legal disputes in the implementation of Umrah pilgrimage, especially related to the management of guarantee funds in the form of deposits which often lead to acts of default. The main focus of this research is to analyze the case in Decision Number : 5/Pdt.G/2025/PN.Tjk.Where the Defendant failed to return the deposit guarantee money for the Plaintiff's Umrah pilgrimage. The purpose of this research is to determine the form of default that occurred and the basis for the judge's consideration in deciding the case. The problem in this research is What is the form of default that occurred in the lawsuit case over the deposit guarantee money for the Umrah pilgrimage and also What is the basis for the judge's consideration in deciding the case of default on the deposit guarantee money for the Umrah pilgrimage based on Decision Number: 5/Pdt.G/2025/PN.Tjk. The research method used in this research is normative juridical and empirical juridical with a library approach and field research through interviews with Judges of the Tanjung Karang District Court and related legal practitioners. Primary data was obtained from trial evidence and interviews, while secondary data came from a study of legal documents.